PENGEMBANGAN BUKU CERITA BERGAMBAR BERBASIS KEARIFAN LOKAL PADA KEMAMPUAN MEMBACA SISWA KELAS III SD - Nurul Hadi Putri; Zariul Antosa Eva Astuti Mulyani; Eva Astuti Mulyani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to produce a valid, feasible, and practical picture storybook based on local wisdom for the reading skills of third-grade elementary school students. This local wisdom-based picture storybook was developed using the Research and Development (R&D) method with Thiagarajan's 4-D model. It passed the validation stage by material and language experts and media experts, with a final percentage score of 89.5% (very valid). Then, the practical stage with teachers and students obtained a final percentage score of 93.35% (very practical). Based on the results of the validation and practicality tests, the developed local wisdom-based picture storybook for the reading skills of third-grade elementary school students is valid and practical and can be used by teachers as a learning reference for students' reading skills.